Analisis Interaksi Guru dan Peserta Didik dengan Social Network Analysis yang Menumbuhkan Minat Belajar di SMK Negeri 1 Tengaran - Joko Listiawan Sukowati; Ade Iriani; Irwan Sembiring (Jurnal Sistem Informasi Bisnis, 2023)
School is a place where students gain knowledge and as a place where the process of interaction between teachers and students occurs.. The interaction between teachers and students greatly influences the learning interests of students. This study aims to find teachers and indicators that influence students' interest in learning in the school environment using Social Network Analysis (SNA). The research was conducted at Tengaran 1 Public Vocational School with the research object being teachers and class XI students. The results showed that the most dominant actor or teacher in degree centrality, which was chosen by the students, was the actor or teacher with the Cp code, with a value of 26. The next step after calculating the SNA and measure network is indicator validation and classification using Naïve Bayes. The results of the indicator validation show that the validation value for each indicator is more than 0.5, so the indicators can be said to be valid. The classification results using naïve Bayes, with a dataset divided by 80% training data and 20% test data showing an accuracy of 85%. It is hoped that the results of this research can be input to teachers so that in schools they are more active in participating in various kinds of activities held by schools, and are active in interacting with students in the teaching and learning process. So, it is hoped that students will be more active in learning.